Evaluation of Mexico's low cancer mortality using two national death registries - Susana Lozano-Esparza; Dalia Stern; Juan Eugenio Hernandez-Avila; Evangelina Morales-Carmona; Alejandro Mohar; Martin Lajous (Instituto Nacional de Salud Pública, 2020)
Objective. To compare cancer mortality rates in Mexico from two national death registries that independently code and attribute cause of death. Materials and methods. We compared 5-year age-standardized total cancer and site-specific cancer mortality rates (2010-2014) from Mexico's official death registry with a death registry from a disease surveillance system. We obtained age-adjusted mortality rates and 95% confidence intervals using the direct method and World Population Prospects 2010 as a standard. Results. Cancer mortality estimates for Mexico were minimally affected by the use of two distinct death certificate-coding procedures. Cancer mortality was 73.3 for Instituto Nacional de Estadística y Geografía and 72.7 for System for Epidemiologic Death Statistics per 100 000 women. The corresponding estimates for men were 68.3 and 67.8. Conclusion. Mexico's low cancer mortality is unlikely to be explained by death certificate processing. Further investigations into the process of death certification and cancer registration should be conducted in Mexico.